2021
DOI: 10.1038/s41598-020-79767-0
|View full text |Cite
|
Sign up to set email alerts
|

Auditory roughness elicits defense reactions

Abstract: Auditory roughness elicits aversion, and higher activation in cerebral areas involved in threat processing, but its link with defensive behavior is unknown. Defensive behaviors are triggered by intrusions into the space immediately surrounding the body, called peripersonal space (PPS). Integrating multisensory information in PPS is crucial to assure the protection of the body. Here, we assessed the behavioral effects of roughness on auditory-tactile integration, which reflects the monitoring of this multisenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Audiotactile interactions have also been shown for roughness perception 19 , and people can reliably judge textural roughness from acoustic cues alone 25 . Moreover, people readily classify sounds in terms of ‘roughness’ 26 28 . In English, the words rough and smooth are two very common descriptors of auditory qualities 29 , and, more generally, touch words are amongst the most frequent adjectives used to describe sound 30 – 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Audiotactile interactions have also been shown for roughness perception 19 , and people can reliably judge textural roughness from acoustic cues alone 25 . Moreover, people readily classify sounds in terms of ‘roughness’ 26 28 . In English, the words rough and smooth are two very common descriptors of auditory qualities 29 , and, more generally, touch words are amongst the most frequent adjectives used to describe sound 30 – 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Neuroscientific research has also identified auditory roughness as a fundamental feature in both screams and artificial alarm signals, as it engages with subcortical structures that are critical to rapidly appraise danger [103]. Another study showed how even in the absence of emotional or social cues, auditory roughness acts as an innate indication of threat, prompting defensive responses in the listeners [104].…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that nonlinear vocal phenomena lowered perceived voice pitch, increased voice darkness and roughness, and caused vocalizers to sound larger, more formidable, and more aggressive. Moreover, in the absence of emotional or social contextual information, auditory roughness per se has been shown to trigger defensive reactions in humans with respect to nonrough stimuli (harmonic tone; Taffou et al, 2021 ). For these reasons, infant-directed vocalizations across cultures tend to be less rough than adult-directed ones (Hilton et al, 2021 ).…”
Section: Auditory Roughnessmentioning
confidence: 99%